“ME CLAVÓ EL VISTO”: YOUNG PEOPLE AND WAITING SCENES IN LOVE REGARDING NEW TECHNOLOGIES - Marentes, Maximiliano; Palumbo, Mariana; Boy, Martín (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2016)
This paper analyzes waiting scenes mediated by new technologies (e.g. Facebook and WhatsApp) in erotic-affective relationships among heterosexual middle-classed young people from the metropolitan area of Buenos Aires. It troubles how this communication channels generate waiting situations marked by (un)control on the own subjectivity and over the loved subject.We use the scenes’ methodological framework as a resource to explore these waiting experiences, a framework that is based on the perspectives of Vera Paiva and Filomena Gregori. We also invoke a multiplicity of sources (fragments of interviews, plays and poems) to enhance the importance of thinking love as a bricolage.This paper consists in three parts. In the first one, we analyze the dynamics and the effects that the situations of waiting related to love have over the subjects. In the second one, there is a reflection on love relationships among young people. In the third one, it troubles how love and waiting scenes are experienced in youth.